Anomaly or Harbinger? Penn State's 1935 Female 'Letter "Man"' and New Frontiers in the History of Women's Intercollegiate Sport in the United States. Issue 17 (12th December 2019) - Slotcavage, Tommy; Dyreson, Mark
Abstract: In 1935, Pennsylvania State University fielded a men's varsity tennis team that included a woman, Dorothy Anderson. In an era in which only college women at single-sex institutions supposedly played intercollegiate sports, Anderson represented a startling anomaly. She briefly became a national celebrity for earning a varsity 'S' from Penn State. Anderson, however, was not merely an anomaly. Inspired by her example, women joined men's tennis varsities at several other colleges in the region from the 1930s through the 1950s, harbingers of a resurrection of women's intercollegiate sports that began in the 1960s and has vastly expanded since the 1970s. Anderson's career illumines a lost history in which previous scholarship has assumed that no women beyond those at women's colleges ever competed while also illustrating the hardships faces by female challengers of gender barriers. In the history of American intercollegiate sport, Anderson paradoxically served as both an anomaly and harbinger.